STRATEGI TRANSFORMASI DIGITAL PADA UMKM KERAJINAN TEMBAGA DAN KUNINGAN TUMANG DALAM MENGHADAPI COVID-19 - Fithri Setya Marwati; Istiatin Istiatin; Raisa Aribatul H; Dimas Ilham Nur R (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2022)
This research has purpose to implement a business digitization strategy in order that micro, small and medium enterprises (MSMEs) are able to survive in the COVID-19 pandemic. The transformation of business digitization was carried out on the MSMEs in copper and brass handicrafts in Tumang Boyolali. This research applied descriptive qualitative method based on survey data of SMEs in copper and brass crafts Tumang Boyolali and the Central Bureau of Statistics. From the results of this research, it can be seen that the business activities of Tumang Boyolali copper and brass SMEs which were carried out using a conventional strategy (Offline System) contributed to a decrease in sales turnover of more than 30%. Meanwhile, the MSME business activities carried out with the MSME business digitization strategy (Online System) such as Smart Phones (PCs or laptops) connected to the internet only amounted to 25% to 38% of MSMEs which experienced an increase in sales turnover. Considering this reason, it is necessary to build infrastructure that supports the digitization of MSMEs in Tumang Boyolali's copper and brass handicrafts in terms of marketing MSME products online